An Ionic Capacitor for Integrated Iontronic Circuits. Issue 4 (4th January 2019) - Janson, Per; Gabrielsson, Erik O.; Lee, Keon Jae; Berggren, Magnus; Simon, Daniel T.
Abstract: Organic electronics, in combination with custom polyelectrolytes, enables solid‐ and hydrogel‐state circuit components using ionic charges in place of the electrons of traditional electronics. This growing field of iontronics leverages anion‐ and cation‐exchange membranes as analogs to n‐type and p‐type semiconductors, and conjugated polymer electrodes as ion‐to‐electron converters. To date, the iontronics toolbox includes ionic resistors, ionic diodes, ionic transistors, and analog and digital circuits comprised thereof. Here, an ionic capacitor based on mixed electron–ion conductors is demonstrated. The ionic capacitor resembles the structure of a conventional electrochemical capacitor that is inverted, with an electronically conducting core and two electrolyte ionic conductors. The device is first verified as a capacitor, and then demonstrated as a smoothing element in an iontronic diode bridge circuit driving an organic electronic ion pump (ionic resistor). The ionic capacitor complements the existing iontronics toolbox, enabling more complex and functional ionic circuits, and will thus have implications in a variety of mixed electron–ion conduction technologies. Abstract : The expansion of the iontronics toolbox is crucial when aspiring for advanced interfaces toward biological systems . Complex iontronic circuitry is needed to communicate at the cellular level, which puts high requirements on the iontronic components. In this work, an ionic capacitor is characterized and integrated as a smoothing capacitor in a four‐diode full‐wave ionic current rectifier.